Best Paper Selection (Yearbook of Medical Informatics, 2017)
Castro GM, Buczkowski L, Hafner JM. The Contribution of Sociotechnical Factors to Health Information Technology-Related Sentinel Events. Jt Comm J Qual Patient Saf 2016 Feb;42(2):70-6 https://linkinghub.elsevier.com/retrieve/pii/S1553-7250(16)42008-8Horsky J, Ramelson HZ. Development of a cognitive framework of patient record summary review in the formative phase of user-centered design. J Biomed Inform 2016 Dec;64:147-57 http://www.sciencedirect.com/science/article/pii/S153204641630137X?via%3DihubKobayashi L, Gosbee JW, Merck DL. Development and Application of a Clinical Microsystem Simulation Methodology for Human Factors-Based Research of Alarm Fatigue. HERD 2016 Jan 1:1937586716673829 http://journals.sagepub.com/doi/abs/10.1177/1937586716673829?url_ver=Z39.88-2003&rfr_id=ori%3Arid%3Acrossref.org&rfr_dat=cr_pub%3Dpubmed&Percival J, McGregor C. An Evaluation of Understandability of Patient Journey Models in Mental Health. JMIR Hum Factors 2016 Jul 28;3(2):e20 http://humanfactors.jmir.org/2016/2/e20/Schnittker R, Schmettow M, Verhoeven F, Schraagen JM. Combining situated Cognitive Engineering with a novel testing method in a case study comparing two infusion pump interfaces. Appl Ergon 2016 Jul;55:16-26 http://www.sciencedirect.com/science/article/pii/S0003687016300047?via%3Dihub